E-Learning Implementation in Islamic Education Innovation - Andi Nurul Hidayat (Hunafa: Jurnal Studia Islamika, 2017)
Rapid development of information technology has influenced various aspects of life including Islamic education, This requires Islamic education institutions to be able to anticipate the developments by practicing learners need-based learning programs.  One way to respond to information technology development is through implementation of e-learning in Islamic education context. Electronic Learning is a new way in teaching and learning process through the uses electronic media such as internet-based learning material.  It is expected e-learning system will be used more effective along with the development of technology and learning methods. The development of the E-learning system is also expected not only take into account the financial and profitability issues, but also learners psychological issues. This reaquires education institutions  to accommodate the different individual personalities and learning strategies.